Bioactivities of phytochemicals in Callistemon citrinus against multi-resistant foodborne pathogens, alpha glucosidase inhibition and MCF-7 cancer cell line - Fayemi, Peter Olutope; Ozturk, Ismet; Kaan, Dilek; Ozcan, Servet; Yerer, Mukerrem Betul; Dokumaci, Alim Huseyin; Ozcan, Ceyda; Uwaya, Gloria Ebube; Fayemi, Omolola Esther; Yetim, Hasan; Yetim, Hasan (TAYLOR & FRANCIS LTD, 2019)
This study investigates in-vitro activities of phytochemicals in Callistemon citrinus against multi-resistant foodborne pathogens, alpha-glucosidase enzyme and MCF-7 cancer cell line. Assays were prepared with lyophilized extracts to determine antioxidant capacity, inhibition of alpha-glucosidase enzyme and growth of foodborne bacteria. Annexin-V detection kit was used for apoptosis detection and FT-IR spectroscopy to confirm structural and functional groups of phytochemicals. Cytotoxicity of the extracts against MCF-7 cells was monitored with xCELLigence Real-Time Cell Analyser. The result from FT-IR analysis gave a peak at 3295 cm(-1) wavenumber, confirming the presence of O-H alcohol functional group. FT-IR analysis also showed the presence of different functional groups such as carboxylic acids, aromatics, alkanes, alcohols, aliphatic amines, alkenes and amine groups in the extracts. Callistemon exhibited strong antioxidant capacities with EC50 values of 0.474 +/- 0.03 and 0.787 +/- 0.15 mL sample/g of 2,2-diphenyl-1-picrylhydeazyl (DPPH) from leaf and flower extracts, respectively. Growth inhibition of most gram-positive foodborne bacteria by phytochemicals from flower extract appeared more promising as an alternative antimicrobial agent for food preservation. IC50 value of 3.69 +/- 0.61 mu g/mL obtained from leaf extract showed its inhibitory potential against alpha-glucosidase enzyme for managing diabetes type-2. A dose response obtained from real-time monitoring with xCELLigence system indicated higher cytotoxicity of the extracts against MCF-7 cell line at >= 200 mu g/mL concentrations within 24 h of incubation. The versatility of phytochemicals in Callistemon observed in this study signifies its potential for enhancing feed or food functionality, moderating blood glucose level and inhibiting the growth of foodborne pathogens or invasive carcinoma in man.
WOS: 000469350100001
Keywords: Antimicrobial; antioxidant; cytotoxicity; diabetes type-2; spectroscopic characterization; xCELLigence system